Uji Efektivitas JamurMetarhizium anisopliae (Metch.) dan Helicoverpa armigera Nuclear Polyhedrosis Virus (HaNPV) terhadap Larva Penggerek Tongkol Jagung Helicoperva armigera Hubner (Lepidoptera: Noctuidae) di Lapangan - Debi Sabrina Ompusunggu; Syahrial Oemry; Lahmuddin Lubis (Jurnal Agroekoteknologi, 2015)
The aim of this research was to know effective concentrationof M. anisopliae and HaNPV to Helicoperva armigera in the field. This research was carried out in Desa Tanjung Makmur Subdistrict Tandem Hulu 1 District Deli Serdang. This research used sampling random technique non factorial with seven treatments and four replications. They were the result showed that the highest larvae population was control (1.35) and the lowest was HaNPV 6g/liter of water (0.10). The highest of attacked intensity was control (38.75% ) and the lowest was HaNPV 6g/liter of water (2.50%). The highest production was HaNPV 6g/liter of water (261.09 g) and the lowest was M. anisopliae 4g/liter of water(234.45 g).Keywords : Helicoverpa armigera, Metarhizium anisopliae, Helicoverpa armigera Nuclear Polyhedrosis Virus (HaNPV).